1982
DOI: 10.1021/jo00134a036
|View full text |Cite
|
Sign up to set email alerts
|

Transition state geometry in super-ene reactions

Abstract: A pseudopericyclic transition state (TS) involving nonlinear H transfer is proposed for the superene reaction (eq 1), characterized by a temperature-independent isotope effect (^h/^d = 2.863). Ancillary evidence for rapid, reversible formation of a four-membered cyclic charge-transfer complex is also presented to account for the observed regio-and stereoselectivity of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been found that the reaction course is considerably different from that in the regular ene. 37 Thus, the superene reaction described by eq 7 is char- over a long temperature range, which is indicative of a bent TS. Ancillary evidence supports the rapid, reversible formation of a four-membered charge-transfer complex between the superene reactants.…”
mentioning
confidence: 99%
“…It has been found that the reaction course is considerably different from that in the regular ene. 37 Thus, the superene reaction described by eq 7 is char- over a long temperature range, which is indicative of a bent TS. Ancillary evidence supports the rapid, reversible formation of a four-membered charge-transfer complex between the superene reactants.…”
mentioning
confidence: 99%
“…Kwart proposed the terminology of 'bent transition states' for superene reactions on the basis of kinetic isotope effects. 24 Precision Density Measurements.-These were carried out as previously described,' yielding the following partial molar volumes in toluene (cm3 mol-I): cyclohexa-1,4-diene (98.0), DEAD (153.4), 2 (217.4); cyclohexa-1,3-diene (98.6), 1 (217.6).…”
Section: (mentioning
confidence: 99%